Width of attached gingiva in an Indian population: A descriptive study - Shaju, Jacob P; Zade, RM (Bangladesh Journal of Medical Science, 2009)
Objectives: Attached gingiva is important for maintaining periodontium in a healthy state. The present study tries to find the normal values of width of attached gingiva in a periodontally healthy Indian population. Material and Methods: The width of attached gingiva was measured with a periodontal probe in periodontally healthy patients attending the periodontics department. Descriptive statistical analysis was done to get the mean, which will represent the normal values of width of attached gingiva for the population. Results: Female patients had a greater width than males and the 20 to 30 year old group had the greatest width of attached gingiva. The mean values of attached gingiva varied in different areas of the mouth with greatest width in maxillary central incisors and least in mandibular molars. Conclusion: Width of attached gingiva varies with age, gender and in different areas of the mouth. Key words: Periodontium, gingiva, health DOI: 10.3329/bjms.v8i3.3985 Bangladesh Journal of Medical Sciences Vol.8(3) 2009 p64-67